Nitrogen-Regulated Group 2 Sigma Factor from Synechocystis sp. Strain PCC 6803 Involved in Survival under Nitrogen Stress - Muro-Pastor, Alicia María (American Society for Microbiology, 2001)
The expression of sll1689, an open reading frame from the cyanobacterium Synechocystis sp. strain PCC 6803 putatively encoding a member of the ς(70) family of sigma factors, appears to be regulated by the nitrogen control transcription factor NtcA. Disruption of sll1689 had no noticeable effect on exponential growth, identifying its product as a member of the group 2, nonessential class of ς(70)-like sigma factors; however, this disruption decreased the viability of the cells after long periods of nitrogen starvation. We have named this gene rpoD2-V. The expression of glnN, encoding a type III glutamine synthetase, was impaired in strains bearing an inactivated copy of the rpoD2-V gene.